Pengaruh Pendekatan Saintifik terhadap Kemampuan Sosial Anak pada Lembaga Pendidikan Anak Usia Dini - Nur Afifah, Risma Nur Afifah; Santa Idayana Sinaga (Universitas Lancang Kuning, 2022)
This study aims to determine the effect of the scientific approach on children's social skills at the Sandalwood Kids Early Childhood Education Institution in Sukomoro, Banyuasin Regency. This type of research is a Pre-Experimental study with the type of One-Group Pretest-Posttest Design by providing treatment using a scientific approach to children, then comparing social abilities in children before and after being given a scientific approach. The method used in collecting research data is through a checklist observation sheet. The research data analysis method is t-test. The study population was all 25 children in group B and the sample in Class B2 was 13 children. The results showed that there was an effect of the scientific approach on social abilities in group B children of Cendana Kids Early Childhood Education in 2022. This can be proven from the results of the calculation of the hypothesis, based on the calculations obtained from the posttest test results of the normality of the data. Then, the variance was recorded uniformly. In addition, after confirming the regularity of the homogeneity of the data carried out, stating that the data is normally distributed and the research variance is homogeneous, the hypothesis is verified from the t test results above the tcount > ttable or 28,562 > 2,179 then reject Ho and accept Ha, the results of this research hypothesis read that there is a significant effect with the use of the scientific approach has an effect on the social abilities of children in Group B Early Childhood Education Cendana Kids.